The Kremlin Colossus. The Ivan the Great bell tower in the urban landscape and the public perception - Atamuratova, Tatiana (Eikonocity. Storia e Iconografia delle Città e dei Siti Europei, 2020)
The Ivan the Great Bell Tower of Kremlin in Moscow in the 19th century was one of the main sights of the city. This paper proposes to address its role in the urban image and public perception in the 19th-early 20th centuries and to use the analysis of texts of guidebooks and travel notes for this purpose. These sources allow to identify a certain synonymity of the names Moscow and Ivan the Great in the public perception. Its height and the location made it the main architectural landmark on the city skyline, a vertical city border and a kind of symbolic unit of measurement.